PEMANFAATAN TEKNOLOGI DALAM PENDIDIKAN ANAK USIA DINI - Septiani Selly Susanti (AZZAHRA, 2020)
This study aimed to described the utilization of technology for early childhood both in the family environment and in the school environment. Because technology can not be separated from the lives of children in this increasingly sophisticated era. The existence of technology can not be denied and however children can not be prevented or prohibited from using it, but the right control and assistance can be the right solution for children. Therefore, this study answers the problems often faced by parents and teachers. This study uses qualitative research with observation and interview techniques in the process of collecting data, as well as using literature study methods from various sources of journals, books, and supporting research results. The study was conducted in Talun, Sumberrejo Bojonegoro district with a total of 20 parents who had children in 3-6 years old and at two of early childhood education institution. The results of this study indicate that the average parents has not provided control and assistance in the using of smartphones to their children, so that childrent spend more time with smartphones than playing with their peers. While in the education, technology has not been maximally utilized by teachers. The results of this study were expected to be a material for teachers and parents in the process of utilizing technology and its application.